Case Report: Whole-Exome Sequencing With MLPA Revealed Variants in Two Genes in a Patient With Combined Manifestations of Spinal Muscular Atrophy and Duchenne Muscular Dystrophy - Xia, Yu; Feng, Yijie; Xu, Lu; Chen, Xiaoyang; Gao, Feng; Mao, Shanshan (Frontiers in Genetics, 2021)
Spinal muscular atrophy (SMA) and Duchenne muscular dystrophy (DMD) are two common kinds of neuromuscular disorders sharing various similarities in clinical manifestations. SMA is an autosomal recessive genetic disorder that results from biallelic mutations of the survival motor neuron 1 gene (SMN1; OMIM 600354) on the 5q13 chromosome. DMD is an X-linked disorder caused by defects in the DMD gene (OMIM 300377) on the X chromosome. Here, for the first time, we report a case from a Chinese family who present with clinical manifestations of both two diseases, including poor motor development and progressive muscle weakness. We identified a homozygous deletion in exon 7 and 8 of the SMN1 gene and a deletion in exon 50 of the DMD gene by whole-exome sequencing (WES) and multiplex ligation-dependent probe amplification (MLPA). This case expands our understanding of diagnosis for synchronous SMA and DMD and highlights the importance of various genetic testing methods, including WES, in differential diagnosis of neuromuscular diseases.